The antecedents and consequences of adolescent fatherhood: A systematic review. (July 2019) - Bamishigbin, Olajide N.; Dunkel Schetter, Chris; Stanton, Annette L.
Abstract: Rationale: Although several systematic reviews have addressed the antecedents and consequences of adolescent motherhood, none have examined adolescent fatherhood. Objectives: The aims of this systematic review were to identify evidence-based factors that increase the probability of adolescent fatherhood and to identify outcomes that differ between adolescent fathers compared to two other groups, namely adult fathers and non-father age peers. The current study used a theoretical framework, Parke's systems view, to guide the review. Method: The search strategy included a bibliographic search of PubMed and PsycINFO. To be included, publications had to be (a) peer-reviewed, (b) quantitative studies, (c) published in English, and (d) compare adolescent fathers (<20 years) to adult fathers (>19 years) or to non-father peers (13- to 19-years old). Results: A total of 2869 unique published sources were screened and 39 met these inclusion criteria. More than half of the articles focused on antecedents ( k  = 24), with the most consistent evidence showing that adolescent fathers come from disadvantaged backgrounds characterized by single-parent households and low parental socioeconomic status. There is also evidence that adolescent fathers were disproportionately Black or Latino (vs. White), had lower academic competence, engaged in more delinquent behavior (e.g., vandalism), and had peers who engaged in more anti-social behaviors. Articles on the outcomes of adolescent fatherhood ( k  = 23) yielded consistent evidence that their offspring are at greater risk of being preterm or low birthweight and psychological disorders as compared to the offspring of adult fathers. Conclusions: Much of the literature was published prior to the year 2000, and methodological weaknesses are noted. Nonetheless, this review has implications for beginning to establish an evidence-based understanding of adolescent fathers. Future rigorous and theory-driven research can provide an even clearer picture and a basis for intervention. Highlights: First systematic review on the risk factors and consequences of teen fatherhood. Teen fathers are disproportionately from minority and low-income households. Teen fathers' offspring are at greater risk of adverse birth outcomes. Most research on teenage fathers outdated; new research is needed. Findings implicate future research and interventions to assist teen fathers.